Beyond Advice: Training Mentors in Ethics, Boundaries, and Trustworthy Mentoring - Dewi Fatmarani Surianto; Asmaul Husnah Nasrullah; Ayu Hasnining; Fhatiah Adiba (PT. Global Research Collaboration, 2025)
The Community Service Program aims to improve ethical competency among student mentors through a structured training program that focuses on five key areas: confidentiality, ethical communication, communication style, professional boundaries, and respecting mentee diversity. A total of 31 mentors participated in pre- and post-test assessments, allowing for a measurable analysis of knowledge development. The training was delivered online using Zoom and included interactive discussions, scenario analysis, and self-reflection sessions. Results showed significant improvements in all five indicators, particularly in understanding ethical communication (from 32.3% to 77.4% selecting the highest score), and appropriate communication style (from 41.9% to 80.6%). Even dimensions with high baseline scores, such as confidentiality (74.2%), experienced positive growth. The findings confirm that the training successfully improved participants’ ethical sensitivity, practical communication skills, and preparedness for real-world mentoring situations. This initiative contributed to the development of a responsible mentoring culture that aligns with the values ​​of empathy, professionalism, and inclusion. Future programs should consider expanding to include peer mentors from other faculties and provide ongoing support mechanisms to strengthen ethical mentoring practices.